Perbedaan Tingkat Kecemasan Ibu Hamil TM III Usia Remaja dan dewasa di Desa Kedawung Wilayah Kerja Puskesmas Ngadi Kecamatan Mojo Kabupaten Kediri - Triatmi Andri Yanuarini; Temu Budiarti; Nurmey Hardyanti Lukitasari (coba, 2015)
Depression is an emotion that has always linked with pregnancy. Anxious positive emotions may face a stressor as a protection, which could be a problem if overdone. Teenage pregnancy with about 20 years of age at risk, often suffer from anemia, impaired fetal development, miscarriage, prematurity, or low birth weight, birth disorders that need surgery labor, pre-eclampsia, antepartum haemorrhage, post-parturition may experience subinvolution uterus, puerperal infection, the formation of and spending less breast milk, the baby may be low IQ. Kedawung contained in abortion incidence in pregnant women aged teens as much as 3 people. Social problems include most unwanted pregnancies that require abortion measures, associated with AIDS disease that requires intensive treatment, psychological not ready to become parents, dropped out of school or work, the birth of a child without a father who jelas.The purpose of this research was to determine differences in the level of anxiety in the third trimester pregnant women teens and adults. The design used comparative analytic with from cross sectional design. The population was all pregnant women TM III adolescence and adulthood in as many as 31 people Polindes Kedawung Mojo Kediri sub district. The sample in this research was 31 respondent using saturated sampling technique. Analysis of the results of research using a statistical (different test) Mann Whitney U-Test with a standard error of 5% (0.05) obtained calculation results U = 32.5 <U a table = 52 so there are differences in the level of anxiety in pregnant women TM III tenn and adults. Women pregnant teen age had higher anxiety than women pregnant adult. Keywords: Anxiety, Pregnancy, Teen and Adult